Pengaruh Keterampilan Berwirausaha Terhadap Niat Berwirausaha Pada Mahasiswa Pendidikan Ekonomi Universitas Sebelas Maret Surakarta - Firsha Jorgie Umarupen (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2019)
The purpose of the authors writing this research is (1) to find out whether there is a positive and significant influence between entrepreneurship skills on attitudes, subjective norms and behavioral control perceptions of Sebelas Maret University economic education students (2) and to find out whether there is a positive and significant influence between attitudes, subjective norms and perceived behavioural control toward the intention of entrepreneurship students of Sebelas Maret University economic education.